Design of Expert System Diagnosis of Catfish Disease with Forward Chaining Method - Erwin Dwi Riyanto; Eko Prasetyo; Rifki Fahrial Zainal; Rani Pubaningtyas; Fardanto Setyatama; Wiwiet Herulambang; Syariful Alim; Rahmawati Febriyaning Tias (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
The expert system can be used as a means for consulting and assisting experts and catfish breeders who areexperiencing problems in identifying catfish diseases and their solutions. So that this expert system can be accessedeasily by anyone and anywhere connected to the internet network, this expert system is made web-based. The MySQLdatabase used in this system will store facts that were built using the PHP programming language. Likewise, systemdevelopment is only limited to diagnosing catfish diseases. The output of this system is in the form of diseaseinformation in catfish and how to handle it. The form of research used by the author is a literature study and is appliedto experimental research. The software development method used by the author is to use the Forward Chaining methodwhich consists of rules. The results of the research that have been made, it is found that this website and expert systemmake it easy for ordinary people or beginners to cultivate catfish in order to produce healthy and superior catfish.